Novel Coumarin Substituted Water Soluble Cyclophosphazenes as Turn-Off Type Fluorescence Chemosensors for Detection of Fe3+ ions in Aqueous Media - (:unkn) unknown (SPRINGER/PLENUM PUBLISHERS, 2015)
In the present work, 3-[2-(diethylamino)ethyl]-7-oxy-4-methylcoumarin substituted cyclotriphosphazene (4) and cyclotetraphosphazene (5) derivatives were synthesized by the reactions of hexachlorocyclotriphosphazene (1) or octachlorocyclotetraphosphazene (2) with 3-[2-(diethylamino)ethyl]-7-hydroxy-4-methylcoumarin (3) for the first time. The quaternized cationic (6 and 7) and zwitterionic (8 and 9) derivatives of these compounds (4 and 5) were obtained by the reactions of dimethyl sulfate and 1,3-propanesultone, respectively. All newly synthesized cyclophosphazene compounds (4-9) were fully characterized by elemental analysis and general spectroscopic techniques such as FT-IR, P-31-NMR, H-1-NMR and MALDI-TOF mass. All these coumarin substituted cyclophosphazene compounds (4-9) were soluble in most of organic solvents and quaternized ionic and zwitterionic compounds (6-9) also showed excellent solubility in water. The fluorescence behaviors of novel cyclophosphazene compounds were investigated in methanol and water solutions. The chemosensor properties of newly synthesized water soluble quaternized ionic and zwitterionic cyclotriphosphazene and cyclotetraphosphazene derivatives (6-9) were investigated in aqueous media. These cyclophosphazene derivatives showed fluorescence chemosensor behavior with high selectivity for Fe3+ ions in aqueous solution.
Keywords: Cyclophosphazene; Coumarin; Water soluble; Chemosensor; Fe3+ ions; DNA INTERACTIONS; CYCLOTRIPHOSPHAZENES; POLYPHOSPHAZENE; PHOSPHAZENES; PROBES; DERIVATIVES; ADDITIVES; CHEMISTRY; BEHAVIOR; LIQUIDS